Highly crystalline, large grain Cu2CoSnS4 films with reproducible stoichiometry via direct solution spin coating for optoelectronic device application. Issue 9 (15th June 2019) - Krishnaiah, Mokurala; Mishra, Rajneesh Kumar; Seo, Seung Gi; Jin, Sung Hun; Park, Jong Tae
Abstract: Highly crystalline, large grain Cu2 CoSnS4 (CCTS) films with reproducible stoichiometry were implemented on thermally oxidized Si wafers and soda lime glass (SLG) substrates via direct solution spin coating. Effects on Cu concentration in the formation of CCTS phase were systematically investigated by X-ray diffraction (XRD) and Raman spectroscopy. Moreover, CCTS films, processed with the optimized Cu concentration (∼8 mmol) and annealing temperature of 575 °C in Ar ambient, exhibit the film morphology with compact, dense, and large grains up to the size of 1.5 μm. The resistivity (ρCCTS ) of CCTS films on SLG and SiO2 substrates were extracted as 7.15 ± 0.18 Ωcm and 7.8 ± 0.19 Ωcm, respectively, denoting that surface roughness and sodium diffusion might affect electrical conductivity of CCTS films. Furthermore, for the optimized CCTS films, noticeable relative photosensitivity (Sph ) up to 20% was achieved under red LED illumination, highlighting that CCTS films could be promising for cost-effective thin film solar cells.